KELAS BALITA : PENINGKATAN KUALITAS MP-ASI DAN MENUMBUHKAN SEMANGAT BERWIRAUSAHA - Ratih Kusuma Wardhani; Ratna Feti Wulandari; Nurin Fauziyah (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Mother Toddler Class can improve the knowledge and skills of mothers who have toddlers in processing complementary foods according to their age-based needs, besides that it can also provide insight related to entrepreneurship material to increase family income. The activity was carried out at the Toddler Posyandu, Pedak Village, Semen District, The target of community service activities was 25 mothers who had babies and toddlers. The activity was carried out in 3 stages, namely the preparation stage, the implementation stage, and the evaluation stage for three days from 15 to 17 December 2021. This service activity used a questionnaire measuring instrument to determine the mother's knowledge about MP-ASI. After being given information and conducting demonstrations on the processing of MP-ASI, 88% of the targets had good knowledge of MP-ASI. This activity was carried out to increase mother's knowledge about complementary feeding and to increase the entrepreneurial spirit. This is done to increase maternal care for infants under five to achieve good nutritional status so as to prevent stunting.